2013
DOI: 10.1017/s0960258513000068
|View full text |Cite
|
Sign up to set email alerts
|

The role of nitric oxide in priming-induced low-temperature tolerance in two genotypes of tomato

Abstract: The present study was conducted to evaluate the contribution of nitric oxide (NO) to the priming effects on seed germination, seedling vigour and lowtemperature tolerance of two tomato cultivars (Solanum lycopersicum, cv. Cherry and Falcato) under four different constant temperatures (10, 15, 20 and 258C). Treatments included priming in a polyethylene glycol 6000 (PEG 6000) solution (osmopriming) or presoaking in sodium nitroprusside (SNP) solution, a donor of NO, for 24 h at 258C. Suboptimal temperatures red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 46 publications
(78 reference statements)
0
20
0
Order By: Relevance
“…Previous studies reported similar results in Triticum aestivum , Sedum alfredii , Eichhornia crassipes , Vallisneria natans and Sesbania drummondii . Increased SOD activity by KNO 3 seed treatment might be due to formation of NO by NR, which also stimulates the seed germination in plant species . However, the activities of CAT, POX and APX were slightly reduced at a higher level of Pb (2550 mg kg −1 Pb) which might be attributed to the increased formation of O 2− , H 2 O 2 and other toxic ROS derivatives that cause inhibition in activity of antioxidant machinery in cell organelles as reported for Coronopus didymus , Eichhornia crassipes , Lycopersicon esculentum and C eratophyllum demersum …”
Section: Discussionmentioning
confidence: 81%
“…Previous studies reported similar results in Triticum aestivum , Sedum alfredii , Eichhornia crassipes , Vallisneria natans and Sesbania drummondii . Increased SOD activity by KNO 3 seed treatment might be due to formation of NO by NR, which also stimulates the seed germination in plant species . However, the activities of CAT, POX and APX were slightly reduced at a higher level of Pb (2550 mg kg −1 Pb) which might be attributed to the increased formation of O 2− , H 2 O 2 and other toxic ROS derivatives that cause inhibition in activity of antioxidant machinery in cell organelles as reported for Coronopus didymus , Eichhornia crassipes , Lycopersicon esculentum and C eratophyllum demersum …”
Section: Discussionmentioning
confidence: 81%
“…NO production was observed in sorghum seeds during germination, even in control samples (Simontacchi, Jasid, & Puntarulo, 2004). In primed tomato seeds, the NO is responsible for the positive effects on seed germination at low temperatures (Amooaghaie & Nikzad, 2013).…”
Section: Discussionmentioning
confidence: 92%
“…Exposure of seeds to abiotic stresses, such as salinity, drought, heavy metals, and chilling, results in lower seed viability, reduced germination, and poor seedling establishment [53,[58][59][60][61]. In addition to enhanced antioxidant capacity, primed seeds show rapid enhancement of /-amylase and/or b-amylase activities, this leads to enhanced starch degradation and sugar accumulation, which in turn results in higher respiration rates, seed viability, germination rates, and seedling establishment than for non-primed seeds [53,[58][59][60][61].…”
Section: Promising Chemicals: Assessment Of Common Components Of the mentioning
confidence: 99%
“…In addition to enhanced antioxidant capacity, primed seeds show rapid enhancement of /-amylase and/or b-amylase activities, this leads to enhanced starch degradation and sugar accumulation, which in turn results in higher respiration rates, seed viability, germination rates, and seedling establishment than for non-primed seeds [53,[58][59][60][61]. Recent evidence suggests that, under conditions of water stress, chemical agents such as PAs may not only enhance the activities of /-amylase and/or b-amylase but may also induce the de novo biosynthesis of b-amylase through elevating b-amylase gene expression at the early stages of seed germination [61].…”
Section: Promising Chemicals: Assessment Of Common Components Of the mentioning
confidence: 99%